Effect of The Problem Solving Learning Toward Critical Thinking Skills in Subject Matter of Global Warming - Adilla, Rika; Ratnawulan, Ratnawulan (PILLAR OF PHYSICS EDUCATION, 2023)
Critical thinking is an active process in which students think about things in more depth for themselves, find relevant information for themselves rather than passively accept things from others. The model of problem-solving is one that can help with activities to develop critical thinking skills. The learning in problem solving can expand the thinking process of students. This research purpose to see wheter there is an impact of the  problem solving learning application on the skills of critical thinking for class X students in lesson global warming.The research type applied in this research was research although quasi-experimental (like an experiment) with research designRandomized Control Grup Pretest-Posttest Design. The research population were all class X.E of SMAN 10 Padang students who were enrolled in 2022/2023. The research sample was class XE 7 as the class for experimental and class XE 6 as the class for control. Sampling was conducted using technique by purposive sampling. Analysis of the research results using statistical methods. The data analyzed were using the two average difference test using the normality and homogeneity tests of the data obtained.Based on the research that has been done and followed by analyzing the research data, the analysis of data shows that the hypothesis was obtained  where 11.26 < 2.00 means HO rejected and H1 is accepted, we got conclussion that there is a significant effect of the  problem solving learning on the skills of critical thinking for class X students in lesson global warming.